2014
DOI: 10.1002/chem.201405800
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Transformation between Cubane and Stairstep Cu4I4 Clusters Using Heat or Solvent Vapor

Abstract: The controlled self-assembly of CuI and an asymmetric ligand with mixed N/S donors, 2-(tert-butylthio)-N-(pyridin-3-yl)acetamide (L), afforded three Cu(I) coordination polymers (CPs), [Cu4I4L2(MeCN)2]n (1), [Cu4I4L2]n (2), and {[Cu4I4L2]⋅MeOH}n (3). X-ray analyses showed that CPs 1-3 are supramolecular isomers with 1, 2, and 3D structures, respectively. CP 1 adopts a stairstep Cu4I4 cluster, whereas CPs 2 and 3 are composed of cubane-like Cu4I4 clusters. Crystal-to-crystal transformations of 1 to 2 and 3 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 58 publications
3
32
0
Order By: Relevance
“…Despite MOF's are being investigated, none of the studies alluded to catalytic properties, one of the driving forces in designing such materials. The reason clearly stems from the fragility of these frameworks as some reports have shown that exchanging solvent crystallization molecules can induced a change in dimensionality [46], or simply decompose at low temperature (see [Cs[Cu 5 I 6 (L13) 2 ] n ), 169°C) [56]. Therefore, the mono-and dithioether assembling ligands are not appropriate for such endeavour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite MOF's are being investigated, none of the studies alluded to catalytic properties, one of the driving forces in designing such materials. The reason clearly stems from the fragility of these frameworks as some reports have shown that exchanging solvent crystallization molecules can induced a change in dimensionality [46], or simply decompose at low temperature (see [Cs[Cu 5 I 6 (L13) 2 ] n ), 169°C) [56]. Therefore, the mono-and dithioether assembling ligands are not appropriate for such endeavour.…”
Section: Discussionmentioning
confidence: 99%
“…When L5 is reacted with CuI in a MeOH/MeCN mixture, a 3D CP of formula [(Cu 4 I 4 )(L5) 2 •MeOH] n is obtained [46]. X-ray crystallography (CSD KOXMAN) reveals the presence of the strongly luminescent Cu 4 I 4 cubane as SBU's and one MeOH crystallization molecule (Fig.…”
Section: Acyclic Ligands Containing Heteroatomsmentioning
confidence: 99%
“…In addition, the arrangement of donor atoms in the ligands may affect both the structures of the complexes and their physical properties. Copper(I) complexes of flexible ligands with N/S donor atoms have been studied (Jeon et al, 2014;Cho et al, 2015). Mechanochromism, vapochromism and solvatochromism of such complexes have also been reported (Kwon et al, 2017;Kang et al, 2015;Kim et al, 2013).…”
Section: Chemical Contextmentioning
confidence: 99%
“…In addition, it is expected that various metal complexes may be formed because they are composed of N/S-donor atoms. In particular, our group reported copper(I) coordination polymers with N/S-donor-atom ligands, which showed their various luminescence and reversible/irreversible structural transformations (Jeon et al, 2014;Cho et al, 2015). As part of our ongoing studies in this area, we designed and synthesized a new N/S-donor ligand, namely N-[2-(cyclohexylsulfanyl)ethyl]quinolinic acid imide, which was prepared from the reaction of quinolinic anhydride with 2-(cyclohexylsulfanyl)ethylamine.…”
Section: Chemical Contextmentioning
confidence: 99%